Interaction of Ferredoxin-NADP Oxidoreductase with the Thylakoid Membrane - Carrillo, Nestor (1982)
The binding of ferredoxin-NADP reductase to spinach chloroplast membranes was studied by washing the membranes with different media. Release of the enzyme from the thylakoids was greater in 0.75 millimolar EDTA but was not complete inasmuch as 20% the activity remained membrane-bound after three washes. A Scatchard plot of binding experiments suggests the presence of one type of binding site and a stoichiometry of 3 to 4 nanomoles of reductase per micromole of chlorophyll was calculated. Rebinding has a nonspecific requirement for cations. Their effectiveness increased with their valency. Rebinding of purified enzyme to depleted membranes resulted in a stimulation of its diaphorase activity. It is suggested that binding of ferredoxin-NADP reductase to thylakoid membranes is dependent upon neutralization of negative charges.